MIKROALGA DIVISI BACILLARIOPHYTA YANG DITEMUKAN DI SUNGAI KASIE KECAMATAN LUBUKLINGGAU BARAT I KOTA LUBUKLINGGAU - Meika Aryani; Linna Fitriani; Harmoko Harmoko; Sepriyaningsih Sepriyaningsih (Florea : Jurnal Biologi dan Pembelajarannya, 2020)
This research is a type of qualitative descriptive research. Data collection techniques by conducting observations, documentation and interviews. The types of microalgae found in the Kasie River Lubuklinggau Barat I Subdistrict, Lubuklinggau City. Bacillariophyta Division consists of one classes, 6 orders, 6 families, 9 genera and 15 spesies. Observed environmental factors: temperature: 27℃, pH: 6,8, Brightness: 0,70 m and dissolved oxygen amount of: 5,03 mg/L. the type of  microalgae division bacillariophyta were found in River Kasie namely: Tabellaria sp, Tabellaria flocculosa, Asterionella sp, Meridion sp, Meridon circulare, Synedra ulna, Synedra rumpens, Synedra sp 1, Synedra sp 2, Surirella linearis, Surirella elegans, Stenipterobia sp, Nitzschia intermedia, Navicula radiosa and Cymbella kappi.